Understanding the Impact of Migration on the Work Ability of Nurses: A Cross-Sectional Comparison Between Germany and Kosovo - Petrit Beqiri; Flaka Siqeca; Rona Karahoda; Vjose Hajrullahu; Olga Agahi; Naime Brajshori (Nursing Reports)
Background/Objectives: Comparative analysis of work ability factors between German nurses without a migration background and Kosovar nurses working in Germany as nurses with a migration background. Methods: This is an observational cross-sectional study. We surveyed 814 nurses from hospitals in Kosovo and Germany using self-administered questionnaires. We used the Nurses Working Capability (WiN) Screening Manual to analyze work ability factors. Data analysis involved descriptive statistics, ANCOVA, and Bonferroni multiple comparison tests. Results: Of the 40 target factors, 17 showed significant differences. There were notable distinctions between German and Kosovar nurses in Germany. Concerning health and personal resources, Kosovar nurses in Germany reported poorer physical (M = 3.71) and social health (M = 3.83) but better mental health (M = 3.53) and fewer cognitive stress symptoms (M = 3.60) than German nurses (M = 3.97, M = 4.05, M = 3.40, and M = 4.00, respectively). As to the work-related factors, Kosovar nurses in Germany faced higher emotional demands (M = 3.33), felt greater time pressure (M = 3.43), and had a more negative view of the organizational structure (M = 2.09) but rated supervisor feedback more positively (M = 3.24) and faced fewer patient-related stressors (M = 2.16) relative to German nurses (M = 2.64, M = 2.64, M = 2.82, M = 2.76, and M = 3.09, respectively). Conclusions: Kosovar immigrant nurses in Germany face distinct challenges related to physical and social health, higher emotional demands, and time constraints; they also have a more negative view of organizational structure than native German nurses. The possible causes of these differences may be attributed to migration-related stress, cultural and environmental adaptations, varying job expectations, or organizational experiences.